AJARAN WUJUDIYAH MENURUT NURUDDIN AR-RANIRI - Rusdiyanto Rusdiyanto; Musafar Musafar (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstract. In the 16th and 17th centuries, the influence and power of Aceh Kingdom reached the sumatra Island and Malay peninsula. Also at that time, Aceh kingdom has acheived a lot of progress in the field of education, the development of thought aprreciation of islmaic teaching. Nuruddin Ar-Raniri is one of immigrant moeslim scholar who take part in the development of Islam in Aceh. His big agenda is to straighten agenda out the understanding of Islam which was brought first by his predecessors, they are Hamzah Fansuri and Syamsuddin as-Samatrani. Their Islamic teaching known by wujudiyah, its close with Ibn Arabi’s mystical understanding or wahdatul wujud. According to ar-Raniri, there are three reasons to oppose this teaching. First, wujudiyah is identic with pre-Islmaic belief such as Christianity, Majusi and Brahmani. Second, Wujudiyah same with splinter sects in Islam that emerged after Prophed died, like Mu’tazilah dan Qadariyyah. Third, wujudiyyah is practices of deviant tarekat from Sunni. His opposition was caused basically he was a Sunni scholars who adheres wahdatus Syuhud’s view. While in fiqh, he is an Asy’ariyah follower. His noncompromise actions against the wujudiyah followers were related to his life in India, which was filled with long intolerant conflicts between Hindus and Muslims.Keywords : Nuruddin Ar-Raniri, Wujudiyyah, Sufism Abstrak. Pada abad ke 16 dan 17 M, pengaruh dan kekuasaan kerjaan Aceh telah sangat terasa di kepulauan Sumatera dan Semenanjung Tanah Melayu. Dalam rentan waktu ini pula, kerajaan Aceh telah mencapai banyak kemajuan, terutama dalam bidang pendidikan, perkembangan pemikiran serta penghayatan terhadap ajaran Islam. Nuruddin Ar-Raniri merupakan salah satu ulama’ pendatang yang ikut mewarnai perkembangan Islam di Aceh. Agenda besarnya adalah meluruskan pemahaman Islam yang terlebih dahulu disebarkan oleh Hamzah Fansuri dan Syamsuddin as-Samatrani. Ajaran yang dikenal dengan nama wujudiyah ini dekat dengan pemikiran sufistik ibn Arabi atau wahdatul wujud. Menurut arRaniri, terdapat tiga alasan mengapa ajaran tersebut perlu ditentang. Pertama Wujudiyah identik dengan agama dan kepercayaan pra Islam seperti Nasrani, Majusi dan Brahmaniyah. Kedua, ajaran Wujudiyah sama dengan ajaran sekte-sekte sempalan dalam Islam pasca Rasulullah wafat, seperti Mu’tazilah dan Qadariyyah. Ketiga, Wujudiyyah merupakan pengamalan dari tarekat yang sesat dan menyimpang dari konsep Islam Sunni. Penentangan ini disebabkan karena pada dasarnya ia adalah ulama’ sunni yang menganut paham Wahdatus Syuhud dalam konsep tasawufnya. Sementara dalam bidang keilmuan lainnya, seperti fikih jelas sekali bahwa ia merupakan Ulama’ sunni yang setia terhadap ajaran Asy’ariyah.Sikap non komprominya kepada terhadap para pengikut wujudiyah dikaitkan dengan kehidupan masa lalunya di India yang hidup dalam konflik berkepanjangan antara Hindu dan Islam yang tidak toleran.Kata Kunci: Nuruddin Ar-Raniri, Wujudiyyah, Tasawuf